Mengatasi Duplikasi Data Dalam Database Menggunakan Metode Eliminasi Data - Dinda Puspita Sari; Septia Amelia; Nadhifa Salsabila Bakris; Nurbaiti Nurbaiti (JUMABI: Jurnal Manajemen, Akuntansi dan Bisnis, 2025)
In the rapidly evolving digital era, data duplication in databases presents a significant challenge that affects storage efficiency, information accuracy, and decision-making quality. This study aims to address the issue of duplicate data through the application of a data elimination method. The method involves a systematic process beginning with data collection, followed by identifying duplicates based on specific attributes, and permanently removing redundant entries using a simple matching approach and SQL programming. The elimination process ensures that each data entry in the database is unique and valid, thereby improving the integrity and reliability of the information system. The results of this study demonstrate that the data elimination method effectively reduces redundancy, enhances database management efficiency, and supports more accurate data-driven decisions. Therefore, implementing data elimination techniques serves as a strategic step in maintaining the quality of information systems across various sectors.